What's in the Literature?. Issue 1 (September 2016) - Silvestri, Nicholas J.; Wolfe, Gil I.; Lacomis, David; Bromberg, Mark B.
Abstract : Abstract: The Guillain–Barré syndrome (GBS) is one of the few neuropathies well known to the general public, in part because of its association with swine flu vaccinations in 1976. GBS has again reached the general public with its possible association with Zika virus. The virus, borne by infected Aedes aegypti mosquitos, is being linked to birth defects when pregnant women are bitten and infected. There are early reports also linking GBS to Zika infection, which could expose a wider range of infected people to the neuropathy. This summer infected Aedes mosquitos will likely reach southern portions of the United States, and travelers to countries where Aedes is endemic will increase. It is important to appreciate that the neurologic consequences of Zika virus are being actively investigated, and firm associations and consequences are yet to be established. Small fiber neuropathies are common and can be due to a number of underlying diseases, and a recent review also indicates that many are idiopathic. One cause is Sjögren syndrome, and a case series reviews clinical features. The diagnosis and underlying features of primary lateral sclerosis are a clinical challenge. Similarities between primary lateral sclerosis and hereditary spastic paraparesis (HSP) have long been noted. With a wide spectrum of gene mutations associated with HSP, clinical distinction between the 2 disorders is problematic. A review covers the wide spectrum of HSP. With no cure, the progression of amyotrophic lateral sclerosis (ALS) to respiratory failure is predictable. This could easily result in marked depression among patients, and 2 studies have explored the frequency and severity of depression. The cause of ALS remains unknown, and when no hereditary factor is apparent, environmental questions arise as possible contributing factor(s). The most notable association is with military service, although specific occupational or environmental linkages are not well sorted out. Two recent reports address these issues. There is good news for ALS patients with muscle cramps with the results of a multicenter randomized and placebo-controlled trial showing that mexiletine is effective in reducing this common symptom. The treatment of myasthenia gravis with various agents, the use of patient-reported outcome measures in myasthenia gravis, and the occurrence of myocarditis in this disease are reviewed. Necrotizing autoimmune neuropathies, the co-occurrence of inclusion body myositis and a form of T-cell leukemia are discussed as are valosin-containing protein (VCP)-opathy and bone health in patients with dystrophinopathy.